The Impact Of Rooming-In On Mother–Infant Bonding Among Postpartum Mothers After Spontaneous And Cesarean Birth - Riris Linda Ayuningrum,; Nining Istighosah,; Reni Yuli Astutik,; Asruria Sani Fajriah,; Suci Anggraeni, (Journal of Health Science Community, 2025)
Efforts to reduce the Infant Mortality Rate (IMR) during the neonatal period include carrying out bonding attachments. There are various ways to support the occurrence of bonding attachment between mother and baby, including the implementation of rooming in and exclusive breastfeeding after delivery (Wijaya et al., 2023). By implementing rooming in, it’s hoped that a good bonding attachment will be created between mother and baby it will have an impact on breastfeeding to support increased achievement of exclusive breastfeeding. This study used a cross-sectional method, with a population of 86 postpartum mothers. Using a purposive sampling technique, the sample was 50 mothers, consisting of 25 spontaneous postpartum mothers and 25 SC postpartum mothers. The results of the study, 84% of postpartum mothers have a good bonding. Based on the Chi-Square test, the result was p=0.000<0.05, H0 was rejected and H1 was accepted, which means there is a relationship between rooming in and bonding attachment in post partum mothers. The distribution of data from 2 groups after the normality test was performed not normal, then a statistical test of the difference between 2 groups using Mann-Whitney U test with the result p = 0.445> 0.05, there was no significant difference between the spontaneous postpartum mother group and the postpartum SC mother group. Hopefully that this research can be developed with a different research design as support for efforts to achieve exclusive breastfeeding.